Crossed ferric oxide nanosheets supported cobalt oxide on 3-dimensional macroporous Ni foam substrate used for diesel soot elimination under self-capture contact mode. Issue 11 (28th October 2015) - Cao, Chunmei; Li, Xingang; Zha, Yuqing; Zhang, Jing; Hu, Tiandou; Meng, Ming
Abstract : Crossed Fe2 O3 nanosheets supported cobalt oxides on three-dimensionally macroporous nickel foam substrate possess particularly high performance for catalytic soot combustion. Abstract : Crossed Fe2 O3 nanosheets supported cobalt oxide nanoparticles on three-dimensionally macroporous nickel foam substrate ( x Co/Fe-NF) was designed and successfully prepared through a facile hydrothermal and impregnation route. These catalysts showed high catalytic soot combustion activities under self-capture contact mode. The three-dimensional macroporous structures of Ni foam and the crossed Fe2 O3 nanosheets constituted macroporous voids can greatly increase the contact efficiency between soot particulates and catalysts. The interaction between Co and Fe facilitated the activation of the Fe–O bond and increased the amounts of active oxygen species, thus improving the redox property of the catalysts. The 0.6Co/Fe-NF catalyst exhibited the highest turnover frequency (TOF) for soot combustion, which is in good accordance with the largest amount of active oxygen species. Based upon the catalytic performance and multiple characterization results, two reaction pathways for soot oxidation are identified, namely, the direct oxidation by the activated oxygen species via oxygen vacancies and the NO x -aided soot oxidation.